Steroidogenesis in ovarian‐like mesenchymal stroma of hepatic and pancreatic mucinous cystic neoplasms. Issue 12 (16th July 2018) - Kumata, Hiroyuki; Murakami, Keigo; Ishida, Kazuyuki; Miyagi, Shigehito; Arakawa, Atsushi; Inayama, Yoshiaki; Kinowaki, Keiichi; Ochiai, Atsushi; Kojima, Motohiro; Higashi, Michiyo; Moritani, Suzuko; Kuwahara, Kyoko; et al.
Abstract : Steroidogenesis in hepatic mucinous cystic neoplasm: Aim: Mucinous cystic neoplasms (MCNs) occur in the ovary, pancreas, and retroperitoneum but very rarely in the liver. Mucinous cystic neoplasms are known to harbor ovarian‐like mesenchymal stroma (OLS) expressing progesterone and estrogen receptors. In this study we evaluated steroidogenesis in OLS of 25 hepatic MCNs and 24 pancreatic MCNs. Methods: Both steroid receptors and steroidogenic factors were immunohistochemically evaluated using H‐scores and results were compared with those in 15 ovarian MCNs and 10 normal ovaries. Results: Androgen receptor (AR) H‐scores in OLS were significantly higher in hepatic, pancreatic, and ovarian MCN than those in normal ovaries. H‐scores of cytochrome P450 17α‐hydroxylase/c17–20 lyase (P450c17) and 5α‐reductase‐1 (5αRED‐1) in the stroma were significantly higher in OLS of hepatic and pancreatic MCN than in the stroma of ovarian MCN and normal ovary. In tumor epithelium, AR H‐scores were significantly higher in hepatic and pancreatic MCN than in ovarian MCN. In both hepatic and pancreatic MCN, a significant positive correlation was detected between AR H‐score in the epithelium and P450c17 H‐score in OLS (hepatic MCN: Pearson's r = 0.446, P  = 0.025; pancreatic MCN: r = 0.432, P  = 0.035). In pancreatic MCN, a significantly positive correlation was detected between AR H‐score in the tumor epithelium and 5αRED‐1 H‐score in OLS (Pearson's r = 0.458, P  = 0.024). Conclusions: These results indicated that locally produced androgens in OLS could be pivotal for tumorigenesis of both hepatic and pancreatic MCN and influence epithelial cells, possibly in a paracrine fashion, which could represent biological significance of OLS in these neoplasms.